2019
DOI: 10.1155/2019/3890906
|View full text |Cite
|
Sign up to set email alerts
|

Human Epididymis Protein 4 (HE4) Reference Limits in Polish Population of Healthy Women, Pregnant Women, and Women with Benign Ovarian Tumors

Abstract: Objectives. Defining precisely the normal range of HE4 protein is crucial for the proper interpretation of tumor marker results and for a more efficient diagnosis of ovarian malignancy. The aim of our study was to evaluate a reference limit of HE4 protein in a population to promote and facilitate the common use of HE4 protein assays. We also tried to identify potential association of HE4 levels with other conditions such as smoking, age, BMI, and creatinine levels. Methods. Blood samples were collected from 61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…On the other hand, Wang et al claimed in their study that HE4 protein levels in first‐ and second‐trimester pregnant women did not change significantly when compared with nonpregnant women, but increased significantly in the third trimester 21 . Gasiorowska et al found that HE4 protein levels were not significantly different in first‐ and second‐trimester pregnancies when compared with each other, while third‐trimester pregnancies had significantly higher HE4 protein levels when compared with the levels in first and second trimester 22 . In the same study, it was concluded that HE4 protein levels increased with increasing age 22 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, Wang et al claimed in their study that HE4 protein levels in first‐ and second‐trimester pregnant women did not change significantly when compared with nonpregnant women, but increased significantly in the third trimester 21 . Gasiorowska et al found that HE4 protein levels were not significantly different in first‐ and second‐trimester pregnancies when compared with each other, while third‐trimester pregnancies had significantly higher HE4 protein levels when compared with the levels in first and second trimester 22 . In the same study, it was concluded that HE4 protein levels increased with increasing age 22 .…”
Section: Discussionmentioning
confidence: 94%
“…Gasiorowska et al found that HE4 protein levels were not significantly different in first‐ and second‐trimester pregnancies when compared with each other, while third‐trimester pregnancies had significantly higher HE4 protein levels when compared with the levels in first and second trimester 22 . In the same study, it was concluded that HE4 protein levels increased with increasing age 22 . In the study of Ratko Delic et al published in 2020, statistically, HE4 protein levels were found within the limits of normal reference values in the first, second, and third trimesters, and serum concentration of the HE4 protein was found to be significantly increased in the third trimester compared to the first and second trimesters 23 .…”
Section: Discussionmentioning
confidence: 98%
“…The non-fluidic array version of the SPRi technique enables the determination of approximately 20 biomarkers without signal enhancement or the preliminary preconcentration of analyte [16,17], which is the advantage of this technique over the fluidic version of SPR. Serous ovarian cancer samples exhibit an HE4 concentration above 150 pM, with maximal values above 850 pM [4], while the marker level for healthy premenstrual women ranges between 15 and 62 pM [18]. The cut-off value for HE4 in serum is recommended at between 70 and 87 pM for premenstrual and between 112 and 140 pM for postmenstrual women, depending on the method used for marker determination [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…All of these studies only investigated healthy pregnant women, one group additionally looked at HE4 serum levels in cases of threatened first trimester miscarriage [16] and another investigated the ROMA index [15]. The results of these studies are partly conflicting as some authors report no difference in HE4 levels in pregnancy [17] or even lower levels than in premenopausal women [13] whereas others confirmed higher HE4 levels with advancing gestation [16,19]. To date, no studies have been published to evaluate interferences of HE4 and CA 125 levels with regard to pregnancy-related conditions and postpartum.…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies have investigated HE4 serum levels in pregnant women 13 , 14 , 15 , 16 , 17 , 18 , 19 . All of these studies only investigated healthy pregnant women, one group additionally looked at HE4 serum levels in cases of threatened first trimester miscarriage 16 and another investigated the ROMA index 15 .…”
Section: Introductionmentioning
confidence: 99%